AWS certified solutions architect associate (SAA-C03). (Packt Publishing, 2023)
The AWS Certified Solutions Architect - Associate certification assesses the skills and knowledge of AWS technology across a wide range of AWS services. This certification focuses on cost and performance-optimized solutions and a strong understanding of the AWS Well-Architected Framework. This course begins with a thorough understanding of the certification program. The AWS Technical Essentials course mirrors the class that AWS offers online. The Technical Essentials course covers terminology and concepts related to the AWS platform, navigating the AWS Management Console, key concepts of AWS security measures and AWS Identity and Access Management (IAM), Amazon Elastic Compute Cloud (Amazon EC2), Amazon Virtual Private Cloud (Amazon VPC), Amazon Simple Storage Service (Amazon S3), Amazon Elastic Block Store (Amazon EBS), Amazon DynamoDB, and Amazon Relational Database Service (Amazon RDS), AWS Auto Scaling, Amazon CloudWatch, and AWS Trusted Advisor. The AWS Certified SAA-C03 exam domains covered include Design Secure Architectures (30%), Design Resilient Architectures (26%), Design High-Performing Architectures (24%), and Design Cost-Optimized Architectures (20%). Upon completion of the course, you will thoroughly understand how to prepare for the AWS SAA-XC03 certification and be prepared for the exam comprehensively. What You Will Learn Learn to navigate the AWS Management Console and AWS terminology Explore AWS security, AWS Identity and Access Management (IAM) Understand Amazon DynamoDB and Relational Database Service (RDS) Explore Amazon Elastic Compute Cloud (EC2) and Virtual Private Cloud (VPC) Know Amazon Simple Storage Service (S3) and Elastic Block Store (EBS) Understand AWS Auto Scaling, CloudWatch, and Trusted Advisor Audience This course is intended for individuals looking to move their business solutions to the AWS Cloud and learn how AWS can help manage costs, security, storage, and computational needs. The course will help you prepare for the AWS Certified Solutions Architect - Associate (SAA-C03) certification and help you pass the exam. The AWS SAA-C03 certification is ideal for those in roles such as a solutions architect, DevOps engineer, Site Reliability Engineer (SRE), data engineer, and senior solutions architect. There are no prerequisite requirements for this course. About The Author Total Seminars: Total Seminars, LLC, is a provider of PC and network repair seminars and certification training services through books, videos, and courseware for thousands of organizations throughout the world including the United Nations, the FBI, and all branches of the US Department of Defense. Mike Meyers is the president and co-founder of Total Seminars, which produces the best-selling CompTIA A+ and Network+ Certification books with over 1 million books in print. He is affectionately called the "Alpha Geek" and is the industry's leading authority on CompTIA Certifications. He has created several other best-selling video courses on CompTIA certifications with the Total Seminars team of instructors. Mike has been involved in the computer and network repair industry since 1987 as a technician, instructor, author, consultant, and speaker. He is the author of numerous popular PC books and videos, including the best-selling CompTIA A+ Certification All-In-One Exam Guide and CompTIA Network+ Certification All-In-One Exam Guide. His humorous and easy-to-follow approach to teaching comes through in his video training courses as well as his classroom instructor-led courses. Making IT concepts easy to understand and fun to learn helps students stay engaged and retain the information. Tom Carpenter: Tom Carpenter is the chief technical officer at CWNP (Certified Wireless Network Professionals). He has been engaged with the IT industry for 25+ years, has published 20 books on IT-related content, and is heavily involved in objective development and exam creation in the certification industry. The author uses AWS daily to run several business websites and operates test labs for content creation and management, among other things. The author delivers course content in a casual and informal structure. He prefers to make the courses fun while you learn the practical applications of AWS. He welcomes individuals to join his classes and plan to use AWS in their personal or professional lives!.